Consumer Satisfaction With Packaging Materials: Kano Model Analysis Approach - Maja Brozović*; Dorotea Kovačević; Josip Bota (Tehnički Vjesnik, 2021)
Packaging can play a significant role in a purchasing decision. Packaging material is one of the most important components of packaging design. It can create an initial impression that may generate an opinion regarding the product's attributes. Despite a significant research focus on packaging, there is a lack of findings related to the consumers' perception of packaging materials. This paper investigates the influence of packaging materials on consumers' perception of product quality according to the Kano model of attributes classification. We used products from the current market which consumers use in daily life and can be commonly found on store shelves. The paper examined 14 quality attributes of different packaging materials using five-level Kano questionnaires. The results indicated that the attributes of particular packaging materials have an effect on the consumers' product choice. In addition, the results demonstrate that the attributes classified as attractive or one-dimensional have a strong impact on the consumers' satisfaction.